It's the Prices, Advanced Capitalism, and the Need for Rate Setting — Stupid. Issue 4 (December 2016) - Frankford, David M.
Competition cannot stem the rise of health care expenditures because it leaves agency diffuse and transferred in part to the institutions of advanced capitalism, which excel in generating demand for their services. The United States should turn to state rate setting to concentrate purchasing power.